(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
: Optical code division multiple access OCDMA is one of the promising optical access technologies due to its worth-mentioning features, such as asynchronous access, and high security. In this paper, the author performed an analytical-based comparison between three commonly used spectrum amplitude coding SAC-based OCDMA codes, namely: Modified Frequency Hopping MFH, Hadamard, and Enhanced Double Weight EDW. The comparison was made based on bit-error-rate BER observation in each case. Matlab was used to conduct this comparison. The results confirm that EDW is the best choice due to its fixed weigh. The only dilemma when adopting EDW code is how to select the proper weight.